Bovine viral diarrhea virus compromises Neutrophil's functions in strain dependent manner. (December 2020) - Thakur, Neelu; Evans, Hannah; Abdelsalam, Karim; Farr, Amanda; Rajput, Mrigendra K.S.; Young, Alan J.; Chase, Christopher C.L.
Abstract: Bovine viral diarrhea virus (BVDV) infection is a major problem that results in economically important diseases of the cattle industry worldwide. The two major consequences of this disease are persistent infection and immune dysfunction. A number of studies have been done to determine the underline mechanisms of BVDV-induced immune dysfunction, in particular targeting antigen-presenting cells, T- and B- cells and cytokine gene expression. However, little research has focused Eon the effect of BVDV on neutrophils. Neutrophils are one of the predominant leukocytes circulating in blood and are considered the first line of defense in the innate immune system along with macrophages. Neutrophils not only eliminate the invading bacteria but also activate innate as well as adaptive immune responses. Therefore, compromised neutrophil function would affect both arms of immune system and caused immune suppression. In the current study, we used virus strains from both BVDV-1 and BVDV-2 species. Including a highly virulent non-cytopathic type 2a BVDV (ncp BVDV2a-1373), moderately virulent non-cytopathic type 2a (ncp BVDV2a 28508-5), and a pair of non-cytopathic type 1b BVDV (ncp BVDV1b TGAN) and cytopathic type 1b BVDV (cp BVDV1b TGAC) strain isolated from a case of mucosal disease. The highly virulent ncp BVDV2a-1373 significantly increased neutrophil apoptosis. However, none of the other BVDV strains affected neutrophil viability. All BVDV strains used significantly reduced CD18 and L-selectin expression on neutrophils as well as their oxidative burst and neutrophil extracellular traps (NET) activity. Cp BVDV significantly reduced neutrophil's phagocytic activity but ncp BVDV did not have any effect on it. On the other hand, ncp BVDV significantly increased neutrophil's CD14 expression and chemotactic activity while cp BVDV did not show any effect either on neutrophil's CD14 expression or on chemotactic activity. In conclusion, BVDV affected neutrophils variability and functional activity in strain dependent manner. Results of the current study will further help in understanding the pathophysiology of different BVDV strains. Highlights: Bovine viral diarrhea virus (BVDV) causes immune dysfunction. The effect of BVDV on the neutrophil, an key cell of the innate immunity, was studied. Highly virulent ncp BVDV2a significantly increased the apoptosis in neutrophils. None of the other strains had any effect. All strains reduced CD18 and L-Selectin surface expression, oxidative burst and neutrophil extracellular traps (NET) activity. Cp BVDV significantly reduced the neutrophil's phagocytic activity but ncp BVDV strains had no effect on phagocytosis. Ncp BVDV significantly increased neutrophil CD14 expression and chemotactic activity while cp BVDV had no effect.